STRENGTHENING CHARACTER EDUCATION BASED ON RELIGIOUS TOLERANCE AMONG PUPILS AT PRIMARY SCHOOL - Ichwan Nurdianto , Mochammad; Akbar, Jamaluddin; Junaidi, Junaidi (Al-Mudarris: Journal Of Education, 2026)
The aim of education is to shape pupils’ character. This study focuses on strengthening character education based on religious tolerance amongst pupils at Speak First Primary School in Klaten. This is a descriptive qualitative study. Data were collected through observation, interviews and documentation. The data obtained in this study were analysed through data reduction, data presentation and drawing of conclusions. The research findings indicate, firstly, the strengthening of self-improvement activities within routine activities: 1) Routine activities include a handshake every morning, daily prayers at the end of lessons led by pupils in turn, communal prayers every Monday, English Day every Tuesday, literacy sessions every Thursday, group exercises every Friday, and the observance of major religious holidays annually. 2) Spontaneous interventions by educators to reprimand pupils exhibiting intolerant behaviour. 3) Educators’ exemplary conduct is grounded in integrity, professionalism, and sincerity. 4) Environmental conditioning through the display of posters and slogans promoting tolerance. Secondly, the reinforcement of religious tolerance character education within the learning process, which is one of the steps to instil a character of tolerance in pupils.